ANALISIS FAKTOR YANG MEMPENGARUHI MENGENAL HURUF DAN MEMBACA SISWA KELAS I SD NEGERI SUMBERMULYO, KEC.SARANG, KAB. REMBANG - Lum Atud Durroh; Aries Tika Damayani; Riris Setyo Sundari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Reading is one of the basic functions of all learning processes, all based on reading while knowing letters, giving children the opportunity to focus more on learning, teaching children how to read in good communication. The formulation of the problem in the context of this research is What are the factors that affect the ability to read and recognize the letters of grade I students of SD N Sumbermulyo?. Research uses qualitative approach methods that are qualitatively descriptive. The subject of this research is a class I student of SD N Sumbermulyo, Kec. Sarang, Kab. Rembang. This research aims to describe events or phenomena with data in the form of information in the form of descriptions from SD N Sumbermulyo, Kec. Sarang, Kab. Rembang. The results of research obtained in the field show that literacy and reading activities applied to class I SD N Sumbermulyo have influential factors in literacy activities. In the ability of students to learn to read and recognize letters in carrying out learning activities, it is still lacking for interest in reading and knowing letters.